Life cycle and nutritional content of pupae of Samia cynthia ricini (Lepidoptera: Saturniidae) feeds on castor and cassava - Ihsan Nurkomar; Dina Wahyu Trisnawati; Saraswati; Rahmadhyta Fitria Fadilah Riali (Penerbit Universiti Kebangsaan Malaysia, 2025)
Utilization of Samia cynthia ricini is still limited to cocoons. Meanwhile, silkworm pupae can be used as an alternative protein source. This research aims to study the effect of diet on the life cycle of S. cynthia ricini fed different diets and analyze the nutritional content of the pupae. The research was conducted by rearing S. cynthia ricini using castor and cassava leaves. The observed variables included survival, life duration, fecundity, and nutritional content of pupae. The results showed that the life duration of S. cynthia ricini fed with castor leaves and those fed with cassava leaves were not significantly different. 85 percent of the S. cynthia ricini population lived until adulthood when fed with castor compared to cassava leaves (65%). Samia cynthia ricini fed with castor leaves also has a 0.318 g cocoon shell weight, heavier than S. cynthia ricini fed with cassava leaves (0.231 g). Adults raised from larvae fed with castor produced 686.6 eggs, more than the cassava leaves treatment (321.6 eggs). Samia cytnhia ricini pupae derived from larvae fed on cassava leaves had higher protein content (73.65%) than castor treatments (55.73%). However, the fat (20.31%), crude fiber (6.64%), carbohydrate (18.35%), and energy (415.55 kcal) contents of pupae derived from larvae fed on castor leaves were higher than those derived from larvae fed on cassava leaves with fat, crude fiber, carbohydrate and energy contents of 14.62%, 5.27%, 5.34%, 374.27 kcal respectively. Using castor leaves in S. cynthia ricini cultivation can enhance production quality and provide pupae with better nutrition than those reared using cassava leaves.